2020
DOI: 10.31577/caosp.2020.50.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Close binaries in hierarchical stellar systems

Abstract: Many (but not all) close binaries are inner pairs in triple and higherorder hierarchical systems. The statistical relation between close binaries and hierarchical systems is well established. Although close binaries can form by a combination of Kozai-Lidov cycles with tides, the study of Moe & Kratter (2018) indicated that only a fraction of them could be produced by this mechanism and that many close binaries form even before stars contract onto the main sequence. The predicted statistical signatures of tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These oscillations can result in the transfer of angular momentum from the inner binary to the third body, leading to changes in the orbital period of the inner binary system. Tokovinin et al (2006) have shown the detailed role of the third bodies in that most spectroscopic binaries with P < 3 days have a tertiary companion (see also Tokovinin 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These oscillations can result in the transfer of angular momentum from the inner binary to the third body, leading to changes in the orbital period of the inner binary system. Tokovinin et al (2006) have shown the detailed role of the third bodies in that most spectroscopic binaries with P < 3 days have a tertiary companion (see also Tokovinin 2020).…”
Section: Discussionmentioning
confidence: 99%